2017
DOI: 10.3389/fspas.2017.00056
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Broad-Band Emission from the Gamma-Ray Emitting Narrow-Line Seyfert-1 Galaxies 1H 0323+342 and B2 0954+25A

Abstract: Prior to the Fermi-LAT era, only two classes of Active Galactic Nuclei (AGN) were thought to harbor relativistic jets that radiate up to gamma-ray energies: blazars and radio galaxies. The detection of variable gamma-ray emission from Narrow Line Seyfert 1 (NLSy1) galaxies has put them on the spotlight as a new class of gamma-ray emitting AGN. In this respect, gamma-ray emitting NLSy1s seem to be situated between blazars (dominated by non-thermal emission) and Seyferts (accretion disc dominated). In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…This confirmed also the scaling laws by Heinz and Sunyaev [80], because it was possible to overlap the jet morphologies of the two objects with the proper scaling [156]. Other studies at different wavelengths are [157][158][159][160][161][162][163][164][165][166][167].…”
Section: Case Studies Individual Objects Anomaliessupporting
confidence: 77%
See 1 more Smart Citation
“…This confirmed also the scaling laws by Heinz and Sunyaev [80], because it was possible to overlap the jet morphologies of the two objects with the proper scaling [156]. Other studies at different wavelengths are [157][158][159][160][161][162][163][164][165][166][167].…”
Section: Case Studies Individual Objects Anomaliessupporting
confidence: 77%
“…It is also worth noting that the search for NLS1s extended to anomalous objects, with uncertain classification. It was suggested that the γ-detected quasar B2 0954 + 25A (z = 0.712) [163,197] [200,201].…”
Section: Case Studies Individual Objects Anomaliesmentioning
confidence: 99%
“…Finally, it is also worth noting the instances in which location of γ-ray emission in the same source changes in different epochs (Foschini et al 2008(Foschini et al , 2011aGhisellini et al 2013;Pacciani et al 2014;Ahnen et al 2015). The similarity of the non-thermal (likely jet-dominated) components of the SEDs of γ-NLS1s and FSRQs seems to suggest that similar processes (i.e., external-Compton dominated γ-ray emission) may be at work in both classes of sources (e.g., Abdo et al 2009a;Berton et al 2016;Arrieta-Lobo et al 2017). Currently, seven FSRQs have been detected by IACTs (Mirzoyan 2017;Mukherjee & VERITAS Collaboration 2017;Cerruti et al 2017;Ahnen et al 2015;Abeysekara et al 2015;Sitarek et al 2015;Aleksić et al 2011;H.E.S.S.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is also worth noting the instances in which location of γ-ray emission in the same source changes in different epochs (Foschini et al 2008(Foschini et al , 2011aGhisellini et al 2013;Pacciani et al 2014;Ahnen et al 2015). The similarity of the non-thermal (likely jet-dominated) components of the SEDs of γ-NLS1s and FSRQs seems to suggest that similar processes (i.e., external-Compton dominated γ-ray emission) may be at work in both classes of sources (e.g., Abdo et al 2009a;Berton et al 2016;Arrieta-Lobo et al 2017) MAGIC Collaboration et al 2008; also see TeVCat 5 for further references). A significant detection of γ-NLS1 by CTA at E 100 GeV would then lead to similar conclusions about the location of the γ-ray emission region, i.e., near the outer edge of the BLR.…”
Section: Discussionmentioning
confidence: 99%
“…Building on previous work [22,23], we utilize a numerical code for modeling the multimessenger (photon and neutrino) emission resulting from a population of accelerated protons and electrons that are injected into a magnetized region and interact with ambient radiation fields and matter. The emission region is a sphere of radius R with a randomly-oriented magnetic field of amplitude B, through which plasma is flowing with velocity v. It is permeated by an external radiation field that serves as target photons for γγ as well as pγ interactions, with a spectrum characteristic of an accretion disk plus hot corona system around a black hole (BH) of mass M BH , total luminosity L disk , and fractional luminosity f cor for the corona [24], and intensity diluted according to the distance z from the BH. It also contains gas with density n g as the target for pp interactions, for which we follow the parameterization of Kelner et al [25].…”
Section: Formulationmentioning
confidence: 99%